BS EN 60674-3-4 Ed.2.0. Specification for plastic films for electrical purposes. Part 3. Specifications for individual materials. Sheets 4 to 6: Requirements for polyimide films used for electrical insulation (5th June 2020) - British Standards Institution,
No abstract available